Studi Literatur Tentang Perspektif Komunikasi Internal Ornganisasi Berkembang - Andi Saputro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Organizations are not formed because of letters or approval documents, but organizations exist from the interactions or specific communications among people that indicate they are organizing. An important aspect of an organization is human resources, which are the people who actively play a role in planning, executing, and controlling to achieve the organization's goals. Human resources are considered the key to success in an organization, because almost every activity carried out uses human resources as labor and an important component in the organization. Effective internal communication is the key to organizational success. However, most academic research on internal communication focuses on large and established companies; however, there are interesting differences in research that looks at newly developing companies. This research will specifically focus on internal communication from the perspective of employees in a developing organization. Research methodology used a systematic literature review with a qualitative approach. The results show that the perspective of organizational internal communication development leading to employee engagement (e.g. employee satisfaction, performance improvement, etc.) is covered in 10 articles. Meanwhile, there are 4 articles that do not clearly depict employees' perspectives on organizational internal communication. Meanwhile, 1 article do not directly discuss how employees perceive internal communication; instead, they explain perspectives towards fellow organization members. The conclusion of study is that the perspective on internal communication, especially among employees in developing organizations, can be linked to performance, satisfaction, and other employees’ engagement. Suggestion for future research could involve using other qualitative methods, especially in startup companies.